Isolation and identification of protease-producing Bacillus amyloliquefaciens LX-6 and its application in the solid fermentation of soybean meal - Huang, Xinyi; Li, Huijie; Han, Tao; Wang, Jiteng; Ma, Zheng; Yu, Xiaoping (Frontiers in Bioengineering and Biotechnology, 2023)
Soybean meal (SM) is considered an ideal substitute for fish meal; however, its application is mainly limited because of its antigen proteins, glycinin and β-conglycinin. To improve the value of SM in the aquaculture industry, we employed an aerobic bacterial strain (LX-6) with protease activity of 1390.6 ± 12.5 U/mL. This strain was isolated from soil samples and identified as Bacillus amyloliquefaciens based on morphological and physiological biochemical characteristics and 16S rDNA gene sequence analyses. Subsequently, we quantified the extent of glycinin and βconglycinin degradation and the total protein and water-soluble protein content after SM fermentation with B. amyloliquefaciens LX-6. At 24 h of fermentation, the macromolecular antigen proteins of SM were almost completely degraded; the maximum degradation rates of glycinin and βconglycinin reached 77.9% and 57.1%, respectively. Accordingly, not only did the concentration of water-soluble proteins increase from 5.74% to 44.45% after 48 h of fermentation but so did the concentrations of total protein and amino acids compared to those of unfermented SM. Field emission scanning electron microscopy revealed that the LX-6 strain gradually disrupted the surface structure of SM during the fermentation process. In addition, B. amyloliquefaciens LX-6 exhibited broad-spectrum antagonistic activity and a wide pH tolerance, suggesting its application in SM fermentation for fish meal replacement.